(3QSGdI aj CMcGe GdMLs - (3eLghds
(3ChdgG (B:s
..... (3hcPG dCgd GdeOjfI Ph GdMdjaI haSQ aj UMjMI GdMdHj HeSLO GdTLQI hdgPG GbJUQ LeY Ydjg hgh bhj hEPG LGhRg aGdLMaI ddQhGjGJ GdUMjMI hbjOg CcKQ GdCUMGH jGdVQhQI hHg NHQ ZjQ faj hGdGMJjGW XGgQ (B...s
(3BNQgG (B:s
... (3eSCdI GTgQ GdML gj ThGd hPh GdbYOI hGdML ceG aj GdQhGJ GdeYJHQI hajd YTQ ef Pj GdMLI hHg QhGjI hGdfRGY GddaXj dG WGFd JMJg , eSCdI jLH GdGJjGf HGdML hGdYeQI aj SfI hGMOI ELeGYG Ydi eG fbdg(B..s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis